1991
DOI: 10.1213/00000539-199112000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Time Required for Oral Ranitidine to Decrease Gastric Fluid Acidity

Abstract: This study documented gastric fluid acidity in ambulatory surgical patients 30-120 min after they had taken a 300-mg tablet of ranitidine, as changes specific to this relatively brief dose-to-sampling interval previously had not been delineated. At 20-120 min before outpatient surgery, ranitidine was given with 15 mL of water to 112 ASA physical status I-III adults without increased risk factors for aspiration of acidic gastric contents. After induction of general endotracheal anesthesia, the gastric fluid was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Jacobs et al [7] found that, 90min after oral administration of ranitidine 300 mg, all patients had a pH > 2.5 but, during the period between 30 and 90 rnin after administration of the same oral dose, 25.6% of the patients had a pH < 2.5. However, no differences were found with respect to volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jacobs et al [7] found that, 90min after oral administration of ranitidine 300 mg, all patients had a pH > 2.5 but, during the period between 30 and 90 rnin after administration of the same oral dose, 25.6% of the patients had a pH < 2.5. However, no differences were found with respect to volume.…”
Section: Discussionmentioning
confidence: 99%
“…ambulatory surgery), it would be practical to shorten this period of time. Jacobs et al [7] have shown that a single dose of ranitidine 300 mg orally provided pulmonary protection 90 min after administration.…”
mentioning
confidence: 99%
“…Oral roxatidine 75 mg was given twice, once at 21:00 on the night before surgery and again 90 min before induction of anesthesia in the present study. Jacobs et al 12 reported that oral ranitidine 300 mg (equivalent to roxatidine 150 mg) consistently prevents acid production when given more than 90 min before induction. However, the data reported by Atanassoff et al 13 suggest that oral ranitidine 150 and 300 mg produce peak gastric elevation of pH (~ 7) at eight and 12 hr following administration.…”
Section: Objectifmentioning
confidence: 99%
“…(8,9) These reports (8,9) also suggest that tolerance to PPI treatment would not develop as PPIs inhibit the H + /K + -adenosine triphosphatase pump, which is the final step in gastric acid secretion from the parietal cell. (10) …”
Section: Introductionmentioning
confidence: 99%